The Politics of Global Indicators in Designing, Promoting and Legitimating the Competition State - Giannone, Diego (PARTECIPAZIONE E CONFLITTO, 2017)
Global indicators of state's performance have grown exponentially over the last three dec-ades. Issues such as economic freedom, competitiveness, property rights, business environment, credit-worthiness, democracy, governance, transparency and media freedom have become central topics of several global benchmarks focused on the evaluation of the state. The objective of this paper is to analyze the reasons behind this phenomenon, investigating the role of those global indicators in world politics and the shaping of an "ideal state". In the first section, the study emphasizes that the global diffusion of rankings and ratings is primarily linked to the rise of neoliberalism. Drawing on Michel Foucault's work on governmentality, global indicators are conceived as specific apparatuses of neoliberal rationality that help to conform states' polities and policies to the twin neoliberal principles of competitiveness and en-trepreneurship. The second section describes the often contradictory construction of the neoliberal com-petition state. Then the study analyzes how the neoliberal state is forged by global indicators. Specifically, the paper focuses on the Global Competitiveness Index by the World Economic Forum. The article ends with some concluding remarks on the power of global indicators and some suggestion for future research.